2016
DOI: 10.1155/2016/2073454
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network of Predictive Motor Timing in the Context of Gender Differences

Abstract: Time perception is an essential part of our everyday lives, in both the prospective and the retrospective domains. However, our knowledge of temporal processing is mainly limited to the networks responsible for comparing or maintaining specific intervals or frequencies. In the presented fMRI study, we sought to characterize the neural nodes engaged specifically in predictive temporal analysis, the estimation of the future position of an object with varying movement parameters, and the contingent neuroanatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Putaminal activity has been traditionally associated with motor preparation and execution, and specifically with the internal generation of precisely timed movements ( Rao et al, 1997 ). Indeed, previous studies ( Filip et al, 2016 ) suggested that the putamen is engaged in the evaluation of success and precision of the undergoing prospective temporal analysis, and our result would underscore its function as a neural node in a network engaged in cases of breaches of temporal expectations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Putaminal activity has been traditionally associated with motor preparation and execution, and specifically with the internal generation of precisely timed movements ( Rao et al, 1997 ). Indeed, previous studies ( Filip et al, 2016 ) suggested that the putamen is engaged in the evaluation of success and precision of the undergoing prospective temporal analysis, and our result would underscore its function as a neural node in a network engaged in cases of breaches of temporal expectations.…”
Section: Discussionsupporting
confidence: 63%
“…Densely connected local clusters were structurally centered on the right middle temporal pole and the right posterior cingulum when the re-orienting effect was specifically considered. The supramodal involvement of the temporal lobe in time processing has been already demonstrated ( Kanai et al, 2011 ; Filip et al, 2016 ), while the posterior cingulate cortex seems necessary for organizing flexible behavior in response to an ever-changing environment. Indeed, this region contributes to signaling environmental changes and, when necessary, to recombining variables into strategy-specific measures of Bayesian evidence that the environment has changed ( Pearson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 86%
“…Cerebellar pathways seem to be largely involved in predictive timing. Indeed, when temporal information inherent to the spatial-temporal trajectory of a dynamic visual stimulus was used to predict its final position, fMRI studies revealed activation in different cortical areas [226,227], and in the cerebellum [228,229].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Research efforts have been increasingly directed towards understanding the patterns of neuronal activity and their behavioural correlate, implicating several regions including cerebellum, basal ganglia, frontal cortex and posterior parietal cortex [ 73 ] in both healthy individuals and specific patient populations. The notion of correct cerebellar function being crucial for successful analysis of temporal information is definitely not new [ 74 ] and it has gained momentum in the recent years, being underscored in neuroimaging [ 75 , 76 ], neurophysiological [ 77 , 78 ] and in clinical studies of patients suffering from varying degree of cerebellar pathology, ranging from predominantly cerebellar defects with deleterious impact on the quality of life [ 79 , 80 ] to categories with plausible, even though often disputed affection of the cerebellum [ 81 ].…”
Section: Cerebellum and Motor Timing In Movement Disordersmentioning
confidence: 99%